2021
DOI: 10.1099/ijsem.0.005119
|View full text |Cite
|
Sign up to set email alerts
|

Microbacterium paulum sp. nov., isolated from microfiltered milk

Abstract: A novel Gram-stain-positive, strictly aerobic, short rod-shaped bacterium, designated 2CT, was isolated from freshly packaged microfiltered milk. This strain was able to grow within the NaCl concentration range of 0–5 % (w/v), temperature range of 8–37 °C (optimally at 30 °C) and at pH 6.0–10.0. Phylogenetic analysis based on 16S rRNA gene sequences revealed that strain 2CT was closely related to species of the genus Microbacterium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
(67 reference statements)
4
11
0
Order By: Relevance
“…In the core genome-based phylogenetic tree ( Figure 2 ), all the Microbacterium strains were resolved into nine major clusters (clusters I–IX including ≥three type strains), and eight minor clusters (clusters X–XVII with two type strains) were defined mostly at GSI of 92 and mean intra-cluster OrthoANIu of >80.00% ( Table 2 ). The topologies of the nine major clusters were maintained irrespective of the addition/deletion of the related sequences and also supported in the core genome analyses reported previously (Dong et al, 2020 ; Bellassi et al, 2021 ; Tian et al, 2021 ). The origin of isolation for each type strain included in the clusters is given in Supplementary Table S3 .…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…In the core genome-based phylogenetic tree ( Figure 2 ), all the Microbacterium strains were resolved into nine major clusters (clusters I–IX including ≥three type strains), and eight minor clusters (clusters X–XVII with two type strains) were defined mostly at GSI of 92 and mean intra-cluster OrthoANIu of >80.00% ( Table 2 ). The topologies of the nine major clusters were maintained irrespective of the addition/deletion of the related sequences and also supported in the core genome analyses reported previously (Dong et al, 2020 ; Bellassi et al, 2021 ; Tian et al, 2021 ). The origin of isolation for each type strain included in the clusters is given in Supplementary Table S3 .…”
Section: Resultssupporting
confidence: 87%
“…Cluster II ( Microbacterium lacticum clade) contains seven species, namely, M. aurum (Yokota et al, 1993a ), M. dextranolyticum (Yokota et al, 1993a ), Microbacterium flavum (Kageyama et al, 2007a ), Microbacterium hominis (Takeuchi and Hatano, 1998a ) , Microbacterium laevaniformans (Dias and Bhat, 1962 ; Collins et al, 1983 ), M. lacticum (Orla-Jensen, 1919 ; Approved Lists, 1980), and Microbacterium paulum (Bellassi et al, 2021 ), and revealed intra-cluster OrthoANIu values≥79.20% (mean, 81.04%) and DNA G+C contents of 69.4–71.0% ( Table 2 ). Most of the type strains were also found as a single cluster in a previous core genome analysis (Bellassi et al, 2021 ), albeit that many of the strains formed well-separated sublines in the 16S rRNA gene trees (Dong et al, 2020 ; Lee and Kim, 2023 ; Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MK, menaquinone; PG, phosphatidylglycerol; DPG, diphosphatidylglycerol; PE, phosphatidylethanolamine; GL, unidentified glycolipids; PL, unidentified phospholipid; L, unidentified lipid. Data were from this study, except for cell morphology, menaquinones, polar lipids and DNA G+C contents of the reference strains[3,8,[35][36][37][38].…”
mentioning
confidence: 99%